Case Report: Post-transplant lymphoproliferative disorder as a serious complication of vascularized composite allotransplantation - Zaccardelli, Alessandra; Lucas, Fabienne M.; LaCasce, Ann S.; Chandraker, Anil K.; Azzi, Jamil R.; Talbot, Simon G. (Frontiers in Transplantation, 2024)
Vascularized composite allotransplantation (VCA) is an emerging field in transplant surgery. Despite overall positive outcomes, VCA confers risk for multiple complications related to the procedure and subsequent immunosuppression. Post-transplant lymphoproliferative disorder (PTLD) is a heterogeneous group of lymphoproliferative disorders occurring after solid organ and hematopoietic stem cell transplant. A patient with PTLD after bilateral upper extremity transplantation is presented as well as a review of all known cases of PTLD after VCA, with a focus on the unique epidemiology, presentation, and treatment in this population.